PENGARUH EKSTRAK KULIT KI-HUJAN, SAMANEA SAMAN, MERRILL TERHADAP AKTIVITAS TRIPSIN - Yusak, Yuniarti
Some researchers found that the extract from Ki-hujan bark, Samanea saman, Merrill, was a toxic alkaloid. The aim of this study was to prove that this toxic alkaloid could inhibit the activity of trypsin. The preparation of these extracts from barks, leaves and seeds, were carried out by extraction of the raw material with a mixture of glacial acetic acid and methanol (1:6). The obtained dried extract was shaken with a mixture of NH4OH and t-butanol (1:1). Then the organic layer was separated and dried at 80Â°C under reduced pressure. The determination of trypsin activity was done spectrophotometrically. The specific activity, was determined as the amount of enzyme activity per mg of enzyme protein, assayed at 35Â°C for 30 min of incubation. The result showed that extracts from Ki-hujan barks, leaves and seeds showed an inhibition of 77.20% for the bark powder (6.67 %), 69.58 % for the bark extract, 68.44 % for the leaf extract, 52.93%for the seed extract (0.53%), 66.87% for the bark extract residue, 62.68% for the leaf extract residue and 49.41% for the seed extract residue(6.67%). The value of Ki in this experiment was 1.90 % in the bark powder, 0.46% in the bark extract, 0.88% in the leaf extract, 1.20% in the seed extract, 0.90% in the bark extract residue, 4.20% in the leaf extract residue and 12.30% in the seed extract residue. It is concluded so far that alkaloids from Ki-hujan tree, have a toxic property and are able to inhibit the activity of trypsin. The structure and physiological activity, will be examined in the next experiment.